2012
DOI: 10.1002/icd.1773
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Social Skills in the Relationship between Motor Ability and Internalizing Symptoms in Pre‐primary Children

Abstract: Impaired motor development can deprive a child of constructive engagement in early motor activities and thus diminish opportunities for the acquisition of key cognitive, social and emotional abilities. The aim of the current study was to test a model where social skills mediate the relationship between motor ability and internalizing symptoms in pre‐primary children. A cross‐sectional research design was employed to assess the mediation model using data from 234 boys and 241 girls aged 4 to 6 years. Structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 74 publications
2
60
0
1
Order By: Relevance
“…Concerning potential buffering effects, it is important to note that both resources are assumed to either mediate or moderate the risk factor-distress relation. To that effect, corresponding cross-sectional research indicates that the relationship between motor coordination and emotional well-being or emotional problems is fully mediated by self-perceptions of competence (Rigoli et al, 2012) and social skills (Wilson et al, 2013) or self-concept (Viholainen et al, 2014), respectively. Corresponding longitudinal research suggests that children with probable DCD are less likely to develop subsequent mental health problems in cases of higher verbal intelligence, self-esteem, academic performance, social communication skills and in the absence of bullying (Lingam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning potential buffering effects, it is important to note that both resources are assumed to either mediate or moderate the risk factor-distress relation. To that effect, corresponding cross-sectional research indicates that the relationship between motor coordination and emotional well-being or emotional problems is fully mediated by self-perceptions of competence (Rigoli et al, 2012) and social skills (Wilson et al, 2013) or self-concept (Viholainen et al, 2014), respectively. Corresponding longitudinal research suggests that children with probable DCD are less likely to develop subsequent mental health problems in cases of higher verbal intelligence, self-esteem, academic performance, social communication skills and in the absence of bullying (Lingam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this category covered developmental coordination disorder (DCD) (Pearsall-Jones et al, 2010, 2011; Pannekoek et al, 2012; Wilson et al, 2013), autism (Kidd and Kaczmarek, 2010), intellectual disability (Povee et al, 2012; Haynes et al, 2013), and attention deficit hyperactivity disorder (ADHD) (Sheikhi et al, 2013). Pearsall-Jones et al (2010) reviewed the etiological pathways of DCD and ADHD and argued that although these developmental disorders tend to overlap and have some shared features such as prevalence and ratio of males to females with the disorders, they have different developmental pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Francis & Piek, 2003;Hill & Brown, 2013;Lingam et al, 2012;Skinner & Piek, 2001;Wagner, Bös, Jascenoka, Jekauc, & Petermann, 2012). Wilson et al (2013) identified a similar relationship whereby social skills mediated the relationship between motor skills and internalizing problems in a community sample of children aged 4 to 6 years. Recent studies which have used community populations have identified a negative association between motor skills and psychosocial factors across the full continuum of motor ability Pearsall-Jones et al, 2011;Rigoli et al, 2016;Wilson et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Rigoli et al, 2012;Rigoli et al, 2016;Wilson et al, 2013). Gender is one variable that has been statistically controlled in most of these studies (e.g.…”
Section: Introductionmentioning
confidence: 99%